2018
DOI: 10.2196/jmir.9367
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Customers’ Experiences With Electronic Prescriptions: Cross-Sectional Survey on Nationwide Implementation in Finland

Abstract: BackgroundOne of the forerunners in electronic health, Finland has introduced electronic prescriptions (ePrescriptions) nationwide by law. This has led to significant changes for pharmacy customers. Despite the worldwide ambition to develop ePrescription services, there are few reports of nationally adopted systems and particularly on the experiences of pharmacy customers.ObjectiveThe aim of this study was to investigate Finnish pharmacy customers’ (1) experiences with purchasing medicines with ePrescriptions;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…This may result from the fact that women and older people tend to respond to surveys more than men and younger adults [49,50]. However, our study respondents' current use of prescription medicines, gender and age distributions were similar to those of earlier Finnish studies conducted among pharmacy customers with similar methods [7,31]. Accordingly, we suggest that the findings of this study can be generalized, with caution, to customers purchasing their prescription medicines at Finnish community pharmacies.…”
Section: Strengths and Limitationssupporting
confidence: 58%
See 1 more Smart Citation
“…This may result from the fact that women and older people tend to respond to surveys more than men and younger adults [49,50]. However, our study respondents' current use of prescription medicines, gender and age distributions were similar to those of earlier Finnish studies conducted among pharmacy customers with similar methods [7,31]. Accordingly, we suggest that the findings of this study can be generalized, with caution, to customers purchasing their prescription medicines at Finnish community pharmacies.…”
Section: Strengths and Limitationssupporting
confidence: 58%
“…Reminders could not be sent because customers were recruited anonymously. A similar method has been successfully used in a few earlier studies targeted at Finnish pharmacy customers [7,30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Since January 2017, all healthcare providers are obliged to use the eprescription system [35]. Community pharmacy customers are familiar and very satisfied with the national service [36,37], and general practitioners report that eprescribing has improved their patient medication management [38,39]. Finnish health professionals have positive expectations about the PAEHR [40].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of e‐prescriptions has been widely studied from the perspectives of healthcare professionals, but less from the other main user group, patients . Studies surveying patients’ experiences have focused on their perceptions of e‐prescriptions, experiences with visiting the pharmacy, experiences with using an online service for viewing e‐prescriptions and satisfaction with the system …”
Section: Introductionmentioning
confidence: 99%
“…Patients’ experiences with e‐prescriptions have been very positive and they rarely encounter any problems with them . Despite this, however, a Swedish survey found that medicine users had only limited knowledge of the nationwide e‐prescription services .…”
Section: Introductionmentioning
confidence: 99%